OC-039 Detection of dysplasia arising in barrett's oesophagus is improved by trained endoscopists with a specialist interest and dedicated lists. (22nd June 2015) - Dunn, JM; Walker, G; Ooi, J; DeMartino, S; O'Donohue, J; Reffitt, D; Meenan, J
Abstract : Introduction: Barrett's oesophagus (BE) is the pre-malignant lesion to oesophageal adenocarcinoma (OAC). The presence of dysplasia, when diagnosed in surveillance programmes, is an important marker of risk of progression and an indication for endoscopic therapy. We have previously demonstrated that BE surveillance technique is variable and suggest centralised lists with few highly trained endoscopists. The aim of this study was to assess the introduction of dedicated BE surveillance lists on dysplasia detection rate (DDR). Method: Prospective study of patients undergoing BE surveillance at two hospitals – district general hospital (DGH), and tertiary referral upper GI centre. A group of 4 endoscopists (group A) were trained in Prague classification, Seattle protocol biopsy technique and lesion detection. They were nominated to undertake BE surveillance, with dedicated time slots or lists. The DDR was then compared with historical data from 47 different endoscopists at GSTT (group B) and 24 at UHL (Group C) who had undertaken Barrett's surveillance over the 5 year period. Analysis was by independent t-tests for continuous variables and chi-squared tests for categorical variables. Results: A total of 729 patients with BE underwent endoscopy, between 2007 and 2012. Results are shown in Table 1 . There was no significant difference in patient's age, sex or length of BE between the three groups. Of these, 21% (30/144) were diagnosed with dysplasia/EAC by group A endoscopists vs. 9% (55/587) in Group B/C (p = 0.0004). There was a significant difference in detection rate of Indefinite or Low grade dysplasia (IND/LGD) and High grade dysplasia (HGD)/EAC between the 2 groups. There was a significant difference in diagnosis of IND in community (25/271) vs. teaching hospital (5/458) (p = 0.0001). Documentation of length of BE by Prague criteria was significantly higher in group A than group B&C. The use of High Resolution Endoscopy was similar between both groups. Conclusion: This study demonstrates that a group of endoscopists trained in BE surveillance, have significantly higher dysplasia detection rate (DDR) than a non specialist cohort. These findings support the argument that BE surveillance, either at DGH or tertiary centre, should only be carried out on dedicated lists by trained endoscopists with a specialist interest. Disclosure of interest: None Declared.